Suspected pulmonary embolism in the first 2,000 incidents reports of perioperative and anesthetic adverse events in Thailand (PAAd Thai) study - Athitarn Earsakul (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND. Background: Perioperative pulmonary embolism (PE) is a rare but life-threatening complication. The diagnosis remains challenging due to non-specific clinical presentations, which may vary from asymptomatic to cardiovascular collapse. Objective: To describe the clinical presentation, diagnosis, and outcomes of the patients after suspected PE as well as to investigate the cause among Thai surgical population. Materials and Methods: The authors conducted an observational study by retrospective analysis of the data from the Perioperative and Anesthetic Adverse Events in Thailand (PAAd Thai) study. All surgical patients under anesthesia in 22 participating hospitals between January 1 and December 31, 2015, were included. The incident reports of suspected PE were reviewed independently by three anesthesiologists. Data regarding patient characteristics, clinical manifestation, and other details were obtained from the standardized incident report forms. Descriptive statistics was used. Results: Of the 2,000 incident reports, 16 patients were diagnosed with suspected PE. Cardiac arrest occurred in 11 cases (68.7%) and the overall mortality rate was 37.5% (6 of 16 patients). Most incidents were reported in orthopedic patients (10 cases, 62.5%) and caused by thrombosis (13 cases, 81.2%). Most of the incidents occurred intraoperatively (10 cases, 62.5%). The confirmatory imaging studies were investigated in eight cases (50%). To minimize the adverse outcomes, having more experience along with the help from experienced assistants and improved multidisciplinary support, were predominantly recommended. In addition, the most frequent suggested corrective strategies were implementation of appropriate clinical practice guideline and quality assurance activity. Conclusion: Perioperative PE causes significant morbidity and mortality. The diagnosis remains difficult but early detection of suspicious clinical presentation and optimization of the treatment are crucial. Identification of high-risk patients, intraoperative vigilance, and effective interdepartmental communication should be considered to improve patient outcomes.